A qualitative study of governance predicament on dengue prevention and control in Malaysia: the elite experience - Abdul Manaf, Rosliza; Mahmud, Aidalina; NTR, Anthony; Saad, Siti Rohana (BMC, 2021)
Background: The challenges faced by healthcare personnel in relation to dengue prevention and control are perennial but noticeably unexplored. It is often difficult to translate policies and decision making by the elite into astute management in consonance with the needs of rank-and-file personnel. In this study, we assess the impact of governance on dengue prevention and control activities in Malaysia as narrated by the elite. Methods: A qualitative study using a case-study approach was conducted between January 2019 and November 2019 in the districts of Gombak and Klang, where the relevant key informants were located. Nineteen interviews were conducted among elite healthcare personnel from different divisions: management, vector, laboratory, inspectorate, health promotion and entomology. Semi-structured interviews were conducted. The sample size was determined through saturation point criteria. Purposive sampling techniques were used to recruit the participants. The interviews were audio recorded, and the transcribed text was analysed with deductive thematic analysis. Results: Data analysis led to the development of 5 themes and 13 categories. The major principles of governance were embodied in a milieu of predicament, linked to constraints but also opportunities. The constraints resulted from inherent determinants of dengue outbreaks, the serviceability of governing policies and the macro-economics of budget allocation. The opportunities to sustain governance at the local operating level stem from a prevalent supportive internal management system, collaborative efforts among corresponding external government agencies and willingness to innovate and embrace novel technology. Conclusion: Elites are influential, often well-informed personnel tasked with making decisions that can reverberate across an organisation, impacting future plans and strategic policies. Political arrangements at higher levels will reflect in advance the tone of how governance in dengue prevention and control is operationalised by entities and individuals at lower levels of the health system. The prevailing centralised structure in the Malaysian health system will continue to entrench the position of the elite and intertwine it with governance and its predicaments.